Warriors - Bruchac, Joseph; Mahone, Ron (Plain City, OH Darby Creek Publishing, 2003)
Jake has left the reservation for Weltimore Academy and entered a different world. Everyone there loves lacrosse, but no one understands it the way Jake does, as an Iroquois. And no one understands Jake either. To the Iroquois, the game of lacrosse was more than recreation, more than competition. It was sacred. Young men and old played for Elder Brother, He Who Loves to Watch the People Play. Jake always remembered this. One of the best players on the reservation, he felt at home with his people and with himself. Then his mother took a job in Washington, D.C., and Jake entered a very different world. Weltimore Academy became his new home, living there as a boarding student while his mom traveled. Others at the school loved lacrosse, too, but not like Jake. Coach Scott trained them hard, offering violent stories about Indians that Jake knew were untrue. How could he make them understand the real game? Until they did, they would never understand him -- or understand the heart of a warrior.
Box -- Creator's game -- Drumbeat -- Deer run -- Weltimore -- Cabinet -- Her decision -- Drills -- Another day --Coach Scott's story -- Game day -- Running home -- Shot -- Secure -- All play -- Warrior's home.
810L
101983
Keywords: Lacrosse; Iroquois Indians; Indians of North America; Boarding schools; Schools; Fiction; Juvenile works